Lipoprotein(a) and ApoB100 Levels as Markers for Diabetic Retinopathy - Nawar Mazin Jawad; Mahmood, Halla; Aber Abdul Amir Mohamad (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
Globally, in individuals of working age, diabetic retinopathy is the leading cause of visual loss. Prior observational research offered contradictory proof for the link between lipoprotein(a) and apoB100 with diabetic retinopathy. The objective of this study was to assess the relationship between lipoprotein(a) and apoB100 with diabetic retinopathy. This study involves 160 patients divided into four groups: non-proliferative diabetic retinopathy (NPDR), proliferative diabetic retinopathy (PDR), controlled type II diabetic patients without retinopathy (NODR), and healthy control persons) in Baghdad-Iraq. An enzyme-linked immunosorbent assay (ELISA) was used to measure lipoprotein(a) and apoB100. Lipoprotein(a) average levels were 30.80±12.28 µg/mL in healthy control patients, 50.92±21.64 µg/mL (p value <0.001, AUC = 0.765, sensitivity = 65, specificity = 90) in NPDR, 56.05±40.89 µg/mL (p value <0.001, AUC = 0.778, sensitivity = 85, specificity = 72.5) in PDR and 29.67±18.57 µg/mL (p value = 0.75, AUC = 0.549, sensitivity = 42.5, specificity = 82.5) in NODR. ApoB100 average levels were 69.28±24.01 ng/ml in healthy control patients, 80.99±20.22 ng/ml (p value = 0.02, AUC = 0.687, sensitivity = 77.5, specificity = 60) in NPDR, 86.44±16.97 ng/mL (p value <0.001, AUC = 0.762, sensitivity = 77.5, specificity = 70) in PDR and 65.89±12.64 ng/mL in NODR (p value = 0.43, AUC = 0.514, sensitivity = 75, and specificity = 70). The study demonstrated that Lipoprotein(a) is the best predictor for proliferative diabetic retinopathy and non-proliferative diabetic retinopathy.